Health‐related quality of life in patients with relapsed or refractory multiple myeloma: treatment with daratumumab, lenalidomide, and dexamethasone in the phase 3 POLLUX trial. (6th April 2021) - Plesner, Torben; Dimopoulos, Meletios A.; Oriol, Albert; San‐Miguel, Jesus; Bahlis, Nizar J.; Rabin, Neil; Suzuki, Kenshi; Yoon, Sung‐Soo; Ben‐Yehuda, Dina; Cook, Gordon; Goldschmidt, Hartmut; Grosicki, Sebastian; et al.
Summary: In the phase 3 POLLUX trial, daratumumab in combination with lenalidomide and dexamethasone (D‐Rd) significantly improved progression‐free survival in patients with relapsed/refractory multiple myeloma (RRMM) compared with lenalidomide and dexamethasone (Rd) alone. Here, we present patient‐reported outcomes (PROs) from POLLUX, assessed using the validated European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30‐item (EORTC QLQ‐C30) and the EuroQol 5‐dimensional descriptive system (EQ‐5D‐5L) questionnaires. Changes from baseline are presented as least‐squares mean changes with 95% confidence intervals (CIs) derived from a mixed‐effects model. PRO assessment compliance rates were high and similar in both D‐Rd and Rd groups through cycle 40 (week 156). In this on‐treatment analysis, mean changes from baseline were significantly greater in EORTC QLQ‐C30 global health status, physical functioning, and pain scores in the D‐Rd group versus the Rd group at multiple time points; however, magnitude of changes was low, suggesting no meaningful impact on health‐related quality of life (HRQoL). Subgroup results were similar to those in the overall population. In the POLLUX study, baseline HRQoL was maintained with prolonged D‐Rd treatment. These findings complement the sustained and significant improvement in progression‐free survival observed with D‐Rd and supports its use in patients with RRMM. Clinical trial registration: NCT02076009.